2022
DOI: 10.1002/admi.202102305
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering with Aluminum Oxide toward an Improved Self‐Powered Narrowband Visible‐Light Photodetection in Lead Halide Perovskite CH3NH3PbBr3/p‐Si Heterojunctions

Abstract: Semiconductor heterojunctions consisting of lead halide perovskite (LHP) and silicon materials are important candidates for the fabrication of self‐powered visible‐light photodetectors. However, the interface recombination caused by interface trap states greatly deteriorates the performance of self‐powered photodetection, but fortunately, it can be suppressed by interfacial engineering. In this work, self‐powered narrowband visible‐light photodetection is demonstrated in the LHP CH3NH3PbBr3/p‐Si heterojunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In recent years, the ion migration behaviors have further been evidenced both by experimental and theoretical investigations. It was shown that halide species (Cl, Br, and I) have the lowest migration barrier height and diffuse with the assistance of grain boundaries and vacancy-type defects. ,, This results in an obvious energy band bending at both ends of the LHP film and subsequently produces the typical I – V hysteresis. For the LHP-based MSM-structured PDs, the effects of ion migration on the photodetection performance have rarely been concerned so far, although great efforts have been made previously, but they mainly focused on improving the photodetection performance of as-fabricated PDs and developing multifunctional (such as flexible, self-powered, and narrow/broad-band detection) devices. In our opinion, the effects of ion migration should be considered in the LHP-based MSM-structured PDs because a bias voltage is necessarily applied, especially for weak light detection. It is worth noting that the ion migration has been observed in the mixed halide CsPbX 3 -based light-emitting diodes recently …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the ion migration behaviors have further been evidenced both by experimental and theoretical investigations. It was shown that halide species (Cl, Br, and I) have the lowest migration barrier height and diffuse with the assistance of grain boundaries and vacancy-type defects. ,, This results in an obvious energy band bending at both ends of the LHP film and subsequently produces the typical I – V hysteresis. For the LHP-based MSM-structured PDs, the effects of ion migration on the photodetection performance have rarely been concerned so far, although great efforts have been made previously, but they mainly focused on improving the photodetection performance of as-fabricated PDs and developing multifunctional (such as flexible, self-powered, and narrow/broad-band detection) devices. In our opinion, the effects of ion migration should be considered in the LHP-based MSM-structured PDs because a bias voltage is necessarily applied, especially for weak light detection. It is worth noting that the ion migration has been observed in the mixed halide CsPbX 3 -based light-emitting diodes recently …”
Section: Introductionmentioning
confidence: 99%
“…However, the PL intensity increases abruptly if the trap states are completely filled. Therefore, the trap state density (n trap ) is proportional to the excitation power threshold of complete trap-filling (P th ) (i.e., n trap ∼ P th [38,39] ). The P th can be obtained by fitting the excitation power dependence of integrated PL spectra with two linear functions, as shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…Narrowband photodetectors are indispensable in machine vision, sensing imaging, and encrypted communication due to high-precision spectral resolution. , Generally, narrowband photodetectors can be realized by the following three strategies: Broadband detectors coupled with bandpass filters or optical microcavity structures. , Absorbing or amplifying specific wavelengths by using materials with narrowband absorption capability or through a plasmonic effect. Regulating the annihilation and collection of photogenerated carriers by the charge collection narrowing (CCN) principle. , In the integration and simplicity of application systems, there are many limitations in strategies (1) and (2), while narrowband photodetectors based on the CCN principle stand out. Recently, CCN-type narrowband photodetectors without filters have been extensively researched in organic–inorganic hybrids, , perovskite thick films, , and two-dimensional/three-dimensional (2D/3D) perovskite single crystals, , and they have been successfully developed in visible, , near-infrared and dual-band narrowband photodetectors. , …”
Section: Introductionmentioning
confidence: 99%
“…8,9 In the integration and simplicity of application systems, there are many limitations in strategies (1) and (2), while narrowband photodetectors based on the CCN principle stand out. Recently, CCN-type narrowband photodetectors without filters have been extensively researched in organic−inorganic hybrids, 10,11 perovskite thick films, 12,13 and two-dimensional/three-dimensional (2D/3D) perovskite single crystals, 14,15 and they have been successfully developed in visible, 16,17 near-infrared 18−20 and dual-band narrowband photodetectors. 21,22 Organic−inorganic halide perovskites have exhibited excellent optoelectronic properties in narrowband photodetectors (PNPDs) such as strong light absorption coefficients, short transit time caused by high carrier mobility, and long charge diffusion length.…”
Section: ■ Introductionmentioning
confidence: 99%